Improving Robot Navigation and Obstacle Avoidance using Kinect 2.0 - Basiri, Amin; Oskoei, Mohammadreza A.; Basiri, Anahid; Shahri, Alireza Mohammad (Digest book (International Conference on Robotics and Mechatronics. Online), 2017)
Kinect is a low-cost controller-free device, originally designed for gaming and entertainment. This work presents a solution using the most recent version of Kinect sensor, which has got significant improvement in several ways in comparison with earlier versions, to cope with one important aspect of autonomous mobile robotics, obstacle avoidance. Modeling the environment based on the point cloud extracted from the depth image data as well as an obstacle avoidance method using the straight line segments and circle arcs, were the main focus of the paper. The environment is represented by a set of polygons and the obstacle avoidance algorithm attempts to find a collision-free path from the current position of the robot to the target pose subject to the shortest possible path considering a safeguard. The whole algorithm was implemented and simulated in V-rep software. A mobile robotic platform based on Pioneer This motivated using the Kinect 2 sensor to extend the ability to detect obstacles and hence to improve the local path planner and obstacle avoidance components.